Tracing Carbonate Formation, Serpentinization, and Biological Materials With Micro‐/Meso‐Scale Infrared Imaging Spectroscopy in a Mars Analog System, Samail Ophiolite, Oman. Issue 11 (28th October 2021) - Leask, Ellen K.; Ehlmann, Bethany L.; Greenberger, Rebecca N.; Pinet, Patrick; Daydou, Yves; Ceuleneer, Georges; Kelemen, Peter
Abstract: Visible‐shortwave infrared (VSWIR) imaging spectrometers map composition remotely with spatial context, typically at many meters‐scale from orbital and airborne data. Here, we evaluate VSWIR imaging spectroscopy capabilities at centimeters to sub‐millimeter scale at the Samail Ophiolite, Oman, where mafic and ultramafic lithologies and their alteration products, including serpentine and carbonates, are exposed in a semi‐arid environment, analogous to similar mineral associations observed from Mars orbit that will be explored by the Mars‐2020 rover. At outcrop and hand specimen scales, VSWIR spectroscopy (a) identifies cross‐cutting veins of calcite, dolomite, magnesite, serpentine, and chlorite that record pathways and time‐order of multiple alteration events of changing fluid composition; (b) detects small‐scale, partially altered remnant pyroxenes and localized epidote and prehnite that indicate protolith composition and temperatures and pressures of multiple generations of faulting and alteration, respectively; and (c) discriminates between spectrally similar carbonate and serpentine phases and carbonate solid solutions. In natural magnesite veins, minor amounts of ferrous iron can appear similar to olivine's strong 1‐μm absorption, though no olivine is present. We also find that mineral identification for carbonate and serpentine in mixtures with each other is strongly scale‐ and texture‐dependent; ∼40 area% dolomite in mm‐scale veins at one serpentinite outcrop and ∼18 area% serpentine in a calcite‐rich travertine outcrop are not discriminated until spatial scales of <∼1–2 cm/pixel. We found biological materials, for example bacterial mats versus vascular plants, are differentiated using wavelengths <1 μm while shortwave infrared wavelengths >1 μm are required to identify most organic materials and distinguish most mineral phases. Plain Language Summary: Imaging spectroscopy from airplanes or satellites helps us to map different rock types on Earth and other planets, using reflected visible to shortwave infrared light. With this technique, each pixel in an image has a corresponding spectrum in hundreds of wavelengths with absorptions that are fingerprints, diagnostic of specific material compositions. Here, we demonstrate how imaging spectroscopy can be used at smaller scales, in the field, in the lab, and on future rover and lander missions. We took an imaging spectrometer to the Samail Ophiolite (Oman), which has many of the same water‐formed minerals and rock types as detected from orbit in some locales on Mars. We determined that imaging spectroscopy can differentiate between minerals that look similar from distance and provide the spatial context of mineral detections to understand the time order of events affecting a rock. Using an imaging spectrometer to find small pieces of unaltered rock left intact after fluids have transformed most of the rock reveals the pressure, temperature, and chemical environment during rock formation and later alteration. Rare minerals and unaltered relicts can then be sampled for intensive study. Plants and bacteria can also be mapped. Such capabilities are useful for environmental investigations on Earth and other planets. Key Points: Meso‐to micro‐scale imaging spectroscopy identifies and maps carbonates, serpentine, and other hydrothermal phases in the Oman ophiolite Pigmentation from multiple types of biological materials including mats in travertine springs are distinguished even in shallow waters Detection thresholds of carbonate and serpentine when mixed can be >20area%, which has implications for interpretation of planetary data